2019
DOI: 10.1002/humu.23697
|View full text |Cite|
|
Sign up to set email alerts
|

New molecular diagnostic trends and biomarkers for amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a rare and fatal neurodegenerative disorder. Two forms are recognized, familial (FALS) that accounts for 5–10% of ALS cases, and sporadic (SALS) that accounts for the rest. Early diagnosis of ALS is important because it improves their therapeutic efficacy. Current diagnosis is based on clinical assessment and requires approximately 12 months, leading to a significant delay in drug administration. Therefore, new methods are required for the earlier diagnosis of ALS. Screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 135 publications
(131 reference statements)
0
25
0
12
Order By: Relevance
“…CD16+56 has been found higher in ALS patients compared to healthy controls 35 . Contrasting results are still reported for Fer 42 or Chol and HDL 43 as biomarkers, nevertheless, some studies suggest that hyperlipidemia is a protective factor in ALS 13 . This could suggest that the aforementioned analytes play a crucial role in differentiating the disease progression regardless of the type of MNDs.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…CD16+56 has been found higher in ALS patients compared to healthy controls 35 . Contrasting results are still reported for Fer 42 or Chol and HDL 43 as biomarkers, nevertheless, some studies suggest that hyperlipidemia is a protective factor in ALS 13 . This could suggest that the aforementioned analytes play a crucial role in differentiating the disease progression regardless of the type of MNDs.…”
Section: Discussionmentioning
confidence: 77%
“…Particularly, neurologists often fail to make a diagnosis of ALS as compared to other MNDs within the first year of illness 11 . The long latency in the differential diagnosis of most ALS/MND cases limits the possibility of a proper therapeutic approach 12,13 . In contrast, an earlier diagnosis reduces the period of uncertainty for the patient allowing them to plan the future care and the essential support, which may have an impact on the progression of the disease 3 .…”
mentioning
confidence: 99%
“…Thus, early diagnosis will enhance therapeutic efficacy. For this, molecular diagnosis of ALS is urgently needed in clinics (Pampalakis et al, 2019). If early drug treatment is combined with patient subgrouping/stratification, it is expected to further extend the clinical benefits of the tested compounds.…”
Section: Discussionmentioning
confidence: 99%
“…TDP-43 aggregates in the cytoplasm of neuronal cells are a common finding in ALS (especially SALS) patients except for patients that carry pathogenic variants in SOD1 (Blokhuis et al, 2013). Intriguingly though, pathogenic variants in >30 genes are responsible for ALS, without including disease modifier genes that significantly increase the heterogeneity of ALS (Pampalakis et al, 2019). Most commonly, mutations occur in C9ORF72 , SOD1 , TDP-43 and FUS genes underly respective FALS forms but are also found in many SALS cases (Zou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies have found that mutations in these genes were mainly identified in familial cases and could explain only approximately 10% of sporadic cases (sALS) [ 6 ]. With next-generation sequencing, novel genes and loci have been increasingly discovered [ 8 ], but the genetics of sALS are not fully understood.…”
Section: Introductionmentioning
confidence: 99%